2021
DOI: 10.15857/ksep.2021.30.1.8
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Foot Reflexology on the Physical Symptoms of Cancer Patients

Abstract: PURPOSE: Foot reflexology has become popular for sustainable health management because it is free from side effects, easy to learn and perform. The purpose of this study was to investigate the effects of foot reflexology on the physical symptoms of cancer patients.METHODS: The systematic review and meta-analysis was conducted by following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Data were pooled using fixed- or random-effects models. Pain, sleep, fatigue, and nausea and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
0
1
Order By: Relevance
“…A review study conducted in 2021 found that foot reflexology did not show significant effectiveness in reducing nausea and vomiting. [ 35 ] These findings contradict the outcomes of our study. The limited sample size and the possibility of requiring more reflexology sessions in the studies may explain this outcome.…”
Section: Discussioncontrasting
confidence: 99%
“…A review study conducted in 2021 found that foot reflexology did not show significant effectiveness in reducing nausea and vomiting. [ 35 ] These findings contradict the outcomes of our study. The limited sample size and the possibility of requiring more reflexology sessions in the studies may explain this outcome.…”
Section: Discussioncontrasting
confidence: 99%